2016
DOI: 10.1016/j.actbio.2016.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Mg2Ag nails augment callus formation during fracture healing in mice

Abstract: Intramedullary stabilization is frequently used to treat long bone fractures. Implants usually remain unless complications arise. Since implant removal can become technically very challenging with the potential to cause further tissue damage, biodegradable materials are emerging as alternative options. Magnesium (Mg)-based biodegradable implants have a controllable degradation rate and good tissue compatibility, which makes them attractive for musculoskeletal research. Here we report for the first time the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 38 publications
4
63
0
1
Order By: Relevance
“…, the determined DRs are in better agreement. The comparison with DRs determined in other in vitro studies shows a large discrepancy (0.47 ± 0.04 mm yr −1 after 7 days, 0.34 mm yr −1 after 3 days, ∼0.6 mm yr −1 after 3 days), due to the difference in flow of the culture medium. While it has been shown in Ref.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…, the determined DRs are in better agreement. The comparison with DRs determined in other in vitro studies shows a large discrepancy (0.47 ± 0.04 mm yr −1 after 7 days, 0.34 mm yr −1 after 3 days, ∼0.6 mm yr −1 after 3 days), due to the difference in flow of the culture medium. While it has been shown in Ref.…”
Section: Discussionmentioning
confidence: 51%
“…In particular, the released concentration of Ag + ions in in vitro experiments was found to be well below toxic concentrations while still antimicrobial efficiency was found . It has been shown in in vivo experiments that the application of Mg‐2Ag implants lead to no difference in the histology of major storage, metabolic and excretion organs …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the corrosion rate of Mg2Ag alloy in vivo was three times faster than in vitro, the alloy still showed sufficient rate of biodegradability which maintained proper mechanical stability while supporting fracture healing. Figure 6 illustrates the X-ray images of fractured bone fixed by steel and Mg2Ag wires during 133 days in mice [113]. Finally, they have concluded that Mg2Ag might be a promising material that has a potential application in musculoskeletal medicine.…”
Section: Recent Developments Of Bm Wires In Bone Applicationsmentioning
confidence: 99%
“…Tie et al [112] introduced a novel Mg alloy containing 2% silver (Mg2Ag) and showed that the alloy possessed appropriate mechanical properties and a rather low degradation rate in vitro. In order to assess the in vivo behavior of the alloy, Jahn et al [113] implanted Mg2Ag intramedullary wires into mice with and without a femoral shaft fracture. The wires with the final diameter of 0.8 mm were produced via the cold rolling following the hot extrusion.…”
Section: Recent Developments Of Bm Wires In Bone Applicationsmentioning
confidence: 99%